Tinjauan Yuridis Terhadap Tindak Pidana Pembunuhan Berencana Dengan Tuduhan Turut Serta Melakukan Pembunuhan Di Kota Makassar (Nomor 776 /Pid.B/2018/PN Mks) (Qawanin Jurnal Ilmu Hukum, 2021)
This research examines the application of the law to the crime of premeditated murder with inclusion and judges' considerations in handling the crime of premeditated murder with inclusion. This research is a normative legal research, the type of data used is secondary data including primary legal materials and secondary legal materials, using literature study data collection techniques. The results showed that the application of the law against the crime of premeditated murder by participating in the conduct that the defendant was accused of committing, ordering and participating in the crime of premeditated murder violated Article 340 of the Criminal Code jo. Article 55 Paragraph (1) 1 of the Criminal Code, where the qualifications of this article are described by the defendant's actions which show that the defendant committed, ordered to do and participated in the crime of premeditated murder. The judge's consideration in handling the crime of premeditated murder with inclusion, from the juridical aspect, the public prosecutor can prove that the defendant was the one who committed, ordered to do and participated in the crime of premeditated murder, from a philosophical aspect, the judge's verdict sentenced him to imprisonment for 15 (five). fifteen) years because it does not provide benefit to the community as the main objective of the law.